Pengelolaan Sampah Melalui Bank Sampah Berkah Di Desa Sucenjurutengah, Bayan, Purworejo - Ana Nur Soimah; Fathin Hidayati; Yoga Umar Toqweka; Nur Ngazizah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This research aims to determine the waste management process and the impact of managing the Berkah Waste Bank in the villages of Sucenjurutengah, Bayan, Purworejo. This research uses a descriptive research model through a qualitative approach. Data collection methods use interviews, observation, video and documentation. Data analysis using this method aims to determine the waste management process and the impact of waste bank management. The Berkah Waste Bank has been running well, namely by using sorting, weighing and depositing methods. As well as Waste Bank administrators who have worked in their respective fields. The impact caused by the management of the Berkah Waste Bank on the environmental aspect is very good because it makes the environment cleaner and waste does not accumulate, on the social aspect the existence of the Waste Bank increases community familiarity, on the economic aspect it is enough to provide additional income for its customers. So, the Waste Bank is the best way to manage waste.